Pembuatan Indeks Surat Kabar Menggunakan Microsoft Word di Perpustakaan Pascasarjana Universitas Negeri Padang (UNP) - Revila, Selvi; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
In this article, the composition of newspaper index at the Library of the Post Graduate Program (PPs) of State University of Padang (UNP) is discussed. This study aims to reveal how to compose the newspaper index. The index creation was accomplished using the Ms-Excel and MS-Word. Data was collected through observation at the Library of PPs UNP. The data was obtained from The Newspaper Clipping of the Library of PPs UNP in 2002 and 2003 as many as 290 articles. The data was in the form of newspaper articles bibliographical data of Kompas, Singgalang, Republika, Media Indonesia, Harian Haluan, and Ganto. The recorded bibliographical data items were the title, name of newspaper, the day of issue, the date of issue, and page. Since the subject of the whole article is educational, the entries of the index were classified by using the third summary of class 370 (education) of DDC. The entries were sorted by the subjects and the titles. The keyword index taken from the words in the article’s title was included in the index.Keywords: newspaper; index; Ms. Word